Stability Constants of Lanthanides(III) Chelates with Substituted Chalcones - Tambatkar, G.D.; Meshram, Y.K.; Gadpayale, M.R.; Bhutada, P.G.; Kurhade, G.H. (Asian Journal of Chemistry, 2010)
The interaction of Ce(III), Pr(III), Nd(III), Sm(III), Gd(III), Dy(III), Yb(III) and Lu(III) metal ions with 2′-hydroxy-(3,4- dioxymethylene)-5′-methyl chalcone (ligand-1) and 2′-hydroxy- 5′-methyl-4-methoxy chalcone (ligand-2) have been investigated by pH-metric technique at 0.1 M ionic strength at 27 ± 0.1 ºC in 70 % dioxane-water mixture. The data obtained were used to estimate the values of proton-ligand stability constant (pK) and metal-ligand stability constant log K. It is observed that Ce(III), Pr(III), Nd(III), Sm(III), Gd(III), Dy(III), Yb(III) and Lu(III) metal ions formed 1:1 and 1:2 complexes with all the ligands.